Bibliometric analysis of opportunities in the halal supply chain: Mapping trends, innovations and industry prospects - Abdul Lateb, Nadiah; Jaswir , Irwandi; Kartika, Betania (Journal of Islamic, Social, Economics and Development, 2024)
In today’s constantly evolving halal ecosystem, understanding the halal supply chain trends and patterns is critical. Despite the expanding significance of the halal supply chain, there is still a lack of comprehensive analysis of how this phenomenon has been accepted and evolved in scholarly study. This gap impedes the development of a comprehensive understanding of the field’s trends, difficulties and future directions. Using a bibliometric analysis, this study investigated scholarly 222 articles on halal supply chains from 2000 to 2023, obtained from Scopus analytics. We utilised tools such as VOSviewer to visualise patterns in author productivity, co-authorship networks and keyword co-occurrence. The analysis is based on the number of publications, author contributions, multidisciplinary nature and worldwide collaboration trends in the subject. This study expects to identify key scholars and their impact on the area, trends in research subjects and the growth of the halal supply chain themes throughout time. This bibliometric analysis research seeks to offer a complete overview of the halal supply chain as an academic area, emphasising its multidisciplinary nature and worldwide impact. By tracing adoption trends and patterns, the study provides valuable insights into the growth of the halal supply chain and its role in influencing the halal economy, directing future research and practices in this vigorous domain.